2021
DOI: 10.1021/acs.joc.1c00103
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Tetrahydrospiro[carbazole-1,3′-indolines] via an InBr3-Catalyzed Domino Diels–Alder Reaction

Abstract: A simple InBr 3 -catalyzed domino reaction of indoles, phenylacetylenes, and various 3-methyleneoxindolines in toluene is described. This reaction not only provided a convenient synthetic protocol for polysubstituted tetrahydrospiro[carbazole-1,3′-indolines] in good yields but also gave completely different diastereoisomers of the tetrahydrospiro[carbazole-1,3′-indolines] to that of the previously reported TfOH-catalyzed one-pot reaction of indoles, acetophenones, and 3-methyleneoxindolines. Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 87 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…From Figures S1–S7, it can be seen that the proton and the carbonyl group in the oxindole scaffold exist on the cis -position in major spiro compounds, while these two groups exist on the trans -position in the minor spiro compound 1n′ . It has been well-known that 3-phenacylideneoxindoles usually have an E -configuration, in which the proton and the carbonyl group exist on the cis -position . Therefore, this result indicated that the retention of the E -configuration was predominately observed in the base-promoted annulation reaction.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…From Figures S1–S7, it can be seen that the proton and the carbonyl group in the oxindole scaffold exist on the cis -position in major spiro compounds, while these two groups exist on the trans -position in the minor spiro compound 1n′ . It has been well-known that 3-phenacylideneoxindoles usually have an E -configuration, in which the proton and the carbonyl group exist on the cis -position . Therefore, this result indicated that the retention of the E -configuration was predominately observed in the base-promoted annulation reaction.…”
Section: Resultsmentioning
confidence: 82%
“…Both bindone and truxenone are useful scaffolds for various polymer materials such as nonlinear optical, organic photovoltaics, and semiconductors. , On the other hand, the facile base-catalyzed Knoevenagel condensation of 1,3-indanedione with aromatic aldehydes afforded more reactive dipolarophilic 2-arylidene-1,3-indanediones, which were widely employed in many Michael addition, Diels–Alder, annulation, and versatile transformation reactions. Recently, we successfully found that the triethylamine-promoted reaction of 1,3-indanedione with 3-arylideneindolin-2-ones in ethanol gave carbamato-substituted indeno­[1,2- a ]­fluorenes, in which the bindone was in situ generated and underwent a further domino reaction process . However, the similar triethylamine-mediated reaction of 1,3-indanedione with 3-phenacylideneoxindoles afforded triindanone-fused spiro­[bicyclo[2.2.2]­octane-2,3′-indoline] derivatives, in which a truxenone derivative was initially formed, and sequentially, the [4 + 2] cycloaddition reaction proceeded. , These reactions clearly indicated that 1,3-indanedione and its oligomers showed diverse reactivity in cycloaddition reaction and that various complex polycyclic compounds can be conveniently synthesized by using readily available starting materials . It is very interesting to investigate the outcome of the cycloaddition reaction of the initially prepared bindone with 3-methyleneoxindoles.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the Diels-Alder reaction of activated 2-vinylindolines or 3-vinylindolines with diverse dienophiles has become the most attractive strategy for the synthesis of carbazole deriv- atives [28][29][30][31][32][33][34][35][36][37][38][39][40]. In recent years, by using the one-pot domino synthetic strategy of in situ-generated 2-vinyl-or 3-vinylindolines and sequential Diels-Alder reaction with activated dienophiles, we have successfully developed several efficient synthetic protocols for diversely functionalized tetrahydrocarbazoles and the corresponding carbazole derivatives [41][42][43][44][45][46][47]. To further demonstrate the synthetic application of domino Diels-Alder reactions and in continuation of our aim to providing efficient domino reactions for the synthesis of biologically important carbazole derivatives [48][49][50][51][52][53], herein we wish to report the DDQ-mediated dehydrogenative Diels-Alder reaction of 3-(indol-3-yl)maleimides and benzoyl-substituted 3-ethylindoles with readily available chalcones for the convenient synthesis of polyfunctionalized carbazole derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Diels-Alder reaction of active 2-vinylindolines or 3-vinylindolines with diverse dienophiles has become the most attractive strategy for the synthesis of many carbazole derivatives [22][23][24][25][26][27][28][29][30][31][32][33][34]. In recent years, by using the one-pot domino synthetic strategy of the in situ generated active 2-vinyl or 3-vinylindolines and sequential Diels-Alder reaction with active dienophiles, we have successfully developed several efficient synthetic protocols for diverse functionalized tetrahydrocarbazole and the corresponding carbazole derivatives [35][36][37][38][39][40][41]. For further demonstrating the synthetic applications of domino Diels-Alder reaction and in continuation our aim to providing efficient domino reaction for synthesis of biologically important carbazole derivatives [42][43][44][45][46][47], herein we wish to report DDQ dehydrogenative Diels-Alder reaction of 3-(indol-3-yl)maleimides and benzoylsubstituted 3-ethylindoles with readily available chalcones for the convenient synthesis of polyfunctionalized carbazole derivatives.…”
Section: Introductionmentioning
confidence: 99%